EFFECT OF WATER CONTENT AND SOIL IMPROVEMENT (HYDROGEL) ON PEAT FIRE SUPPRESSION - Muizzaddin, Muizzaddin; Bernas, Siti Masreah; Sarno, Sarno (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2021)
Forest and land fires are Indonesia's biggest problem which has continued from 2014 to the present. The number of activities to find the best solution in fire is something that has been done until now. Various methods, both preventive and repressive, have been implemented to prevent forest and land fires from occurring. This research aims to be a sureextinguishing gel, namely hydrogel, which can be used in efforts to extinguish forest and land fires. Extinguishing forest and land fires using hydrogel is a new method that is expected to prevent forest and land fire zones from spreading. This research shows that the tendency of decreasing the average water content of peat due to the drying process based on different intervals of oven time, namely the lowest yield ranged from 61.25% to the highest with a water content of 109.57%.